2017
DOI: 10.24959/cphj.17.1431
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of application of the complex with artichoke and garlic in clinical medicine

Abstract: Національний фармацевтичний університет ПАТ НВЦ «Борщагівський ХФЗ»* Перспективи застосування в клінічній медицині комплексу артишоку та часникуПрепарати рослинного походження набувають у сучасному світі все більшої популярності через властиві їм пе-реваги порівняно з ліками хімічного походження. Тривалий історичний досвід застосування, високий профіль безпеки, комплексність впливу і можливість тривалого застосування без істотних побічних явищ обумовлю-ють ріст їх споживання у всьому світі. Але практика викори… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The risk of CHD in patients with Hyperlipidemic T2DM (HT2DM) is doubled high than in non-diabetic patients [2]. Several studies showed a correlation between HT2DM, CHD, and metabolic syndrome (MetS) with elevated oxidative stress biomarkers and high-sensitivity C-Reactive Protein (hs-CRP) (3,4). Lifestyle changes (i.e., supplementation and exercise) are among the complementary therapeutic approaches in patients with HT2DM [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of CHD in patients with Hyperlipidemic T2DM (HT2DM) is doubled high than in non-diabetic patients [2]. Several studies showed a correlation between HT2DM, CHD, and metabolic syndrome (MetS) with elevated oxidative stress biomarkers and high-sensitivity C-Reactive Protein (hs-CRP) (3,4). Lifestyle changes (i.e., supplementation and exercise) are among the complementary therapeutic approaches in patients with HT2DM [1].…”
Section: Introductionmentioning
confidence: 99%
“…Convincing evidence showed that Aerobic Training (AT) has the potential to enhance weight loss, increase the Glucose transporter type 4 (GLUT4) abundance, and improve metabolic status in these patients [2,3]. Turmeric, with the scientific name of Curcuma longa, is used in traditional Chinese medicine [4] that contains polyphenols, flavonoids, and tannins and is proposed to have anti-diabetic properties [5][6][7]. Turmeric Supplementation (TS), probably via improving Total Antioxidant Capacity (TAC) [8] and hs-CRP, plays an inhibitory role in the development of inflammation in different disease conditions [9].…”
Section: Introductionmentioning
confidence: 99%